REFORMULASI PERBUATAN MELANGGAR HUKUM OLEH BADAN ATAU PEJABAT PEMERINTAHAN DALAM KONTEKS KOMPETENSI ABSOLUT PERADILAN TATA USAHA NEGARA - Agus Budi Susilo (Jurnal Hukum dan Peradilan, 2013)
Agency or government officials have broad authority in implementing government affairs. Broad authority was likely to be abused , causing loss and injustice in the society as well as lower level government officials, therefore there must be other institutions that control it. Based on the theory of triad politics, the executive is politically controlled by the legislature and are legally controlled by the judiciary, because the agency or government officials running the executive function, which controls the judiciary juridical is the State Administrative Court ( Judicial TUN ). TUN judicial control by the Court at this time is so vague, because it is limited by the law on the Judiciary TUN revised twice (Law No. . 5 of 1986 which was later revised by Law No. . 9 of 2004 and Act No. . 51 of 2009 ) . Testing is limited to understanding the Administrative Court Administrative Decision ( KTUN ) in the strict sense. It can be said that the law on the Judiciary TUN philosophically opposed to the purpose of the establishment TUN Judicial institutions, namely resolve administrative disputes in a broad sense. Therefore, based on futuristic ideas that need to be explored further in the TUN Courts abolut authority to exercise control or testing for unlawful acts committed government agencies or officials. All this is nothing else aims to reposition back nature of administrative law enforcement by the state Judicial TUN and simplify all the administrative state dispute settlement based on the principles of effectiveness and efficiency. Keyword; Deeds Against the Law, Government Officials, Administrative Court